2019
DOI: 10.1186/s12889-019-6713-5
|View full text |Cite
|
Sign up to set email alerts
|

Influenza epidemiology and influenza vaccine effectiveness during the 2016–2017 season in the Global Influenza Hospital Surveillance Network (GIHSN)

Abstract: Background The Global Influenza Hospital Surveillance Network (GIHSN) aims to determine the burden of severe influenza disease and Influenza Vaccine Effectiveness (IVE). This is a prospective, active surveillance and hospital-based epidemiological study to collect epidemiological data in the GIHSN. In the 2016–2017 influenza season, 15 sites in 14 countries participated in the GIHSN, although the analyses could not be performed in 2 sites. A common core protocol was used in order to make results c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 14 publications
7
20
0
2
Order By: Relevance
“…Finally, our RT-PCR results showed that influenza A(H1N1) pdm09 virus was the predominant strain in our population, coinciding with other studies reporting a high circulation of this strain in Mexico during the same period (Baselga-Moreno et al, 2019), while most other Northern Hemisphere countries reported a predominance of influenza AH3N2 virus (Pebody et al 2017;Mira-Iglesias et al 2018;Wu et al 2018;Baselga-Moreno et al, 2019;Flannery et al, 2019). Interestingly, the incidence of influenza B in our study was higher than previous local seasonal averages (Cortes-Alcala et al 2018;Fernandes-Matano et al 2019), but contrasts with official national statistics showing a lower incidence of influenza B during the same period (Secretaria de Salud and Dirección General de Epidemiología, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, our RT-PCR results showed that influenza A(H1N1) pdm09 virus was the predominant strain in our population, coinciding with other studies reporting a high circulation of this strain in Mexico during the same period (Baselga-Moreno et al, 2019), while most other Northern Hemisphere countries reported a predominance of influenza AH3N2 virus (Pebody et al 2017;Mira-Iglesias et al 2018;Wu et al 2018;Baselga-Moreno et al, 2019;Flannery et al, 2019). Interestingly, the incidence of influenza B in our study was higher than previous local seasonal averages (Cortes-Alcala et al 2018;Fernandes-Matano et al 2019), but contrasts with official national statistics showing a lower incidence of influenza B during the same period (Secretaria de Salud and Dirección General de Epidemiología, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…We also evaluated the VE of 2016/17 influenza vaccines. Our overall VE estimates against any type of influenza were lower compared to the previous season (Jackson et al 2017) and almost similar to estimates from other Northern Hemisphere countries that also showed a low VE of the 2016/17 vaccines (Pebody et al 2017;Mira-Iglesias et al 2018;Wu et al 2018;Baselga-Moreno et al, 2019;Flannery et al, 2019). Our results also showed that VE against influenza AH3N2 virus was higher in children and young adults compared to older patients during the evaluated season (Kissling et al 2017;Pebody et al 2017;Wu et al 2018;Flannery et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…During the 2017-2018 in uenza season, in uenza accounted for approximately one-third of hospital admissions with in uenza-like symptoms, which agrees with previous in uenza seasons in the GISHN, where proportions were between 21% and 31% [8][9][10]17]. As in previous studies, all strains of in uenza were detected, with widely varying strain circulation between sites and even neighboring regions.…”
Section: Discussionsupporting
confidence: 90%
“…Isolation of RNA from the influenza viruses was carried out using the QIAamp® Viral RNA Mini Kit (QIAGEN, Germany) according to the manufacturer's instructions. The reaction mixture for PCR was prepared according to the method for the detection of swine and seasonal A(H1N1)pdm09 influenza viruses as recommended by the CDC (Atlanta, USA) [17]. For the PCR, the Ambion AgPath-IDTM One-Step RT-PCR Kit and a set of primers and probes (Thermo Fisher Scientific, USA) were used.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%